Learning Evaluation: Students’ Perception of Online English Courses with a Focus on Writing and Reading Material - Helmy Sahirul Alim; Milawati Milawati; Nurir Rohmah (IKIP PGRI Pontianak, 2021)
The government issued a policy to conduct the teaching and learning process through online due to the covid-19.The class has experienced a shift in methods which previously made a direct observations to distance observation. Evaluation is one of the important components and stages that must be taken by teachers to determine the effectiveness of learning.The purpose of this study was to find out how students' perceptions (1) problems, (2) Satisfaction and (Effectiveness) as students in Shipbuilding Engineering semester 3 at PoliteknikNegeri Madura for online class with a focus on writing and reading materials.This study used a descriptive research with a quantitative approach due to its relation to the type of data and its analysis. (1) the data obtained shows that 93.3% of students have the main obstacle in taking online English classes is signal problems and 6.7% of students have sound and visibility problems when the class takes place. (2) the data showed that 50% of students choose the sufficient option, 43.3% choose satisfied and the remaining 6.7% choose less satisfied. (3) the data showed that 60% of students choose the quite effective option, 33.3% choose effective and the remaining 6.7% choose less effective.